Effect of stress tolerance endophytic bacteria on the growth of Andographic paniculata under abiotic stress - Somal, Manpreet Kaur; Karnwal, Arun (Journal of Postharvest Technology, 2022)
The present study focuses on the effect of endophytic bacteria on the growth of Andographic paniculata grown at an altitude of 786ft under  salt and heavy metal stress. The seeds were inoculated with the two endophytic bacteria Solibacillus silvestris DL3R2 and Pelomonas  aquatica AIS1S isolated from Abutilon indicum and Hermocallis fulva. The seeds were inoculated with the two endophytic bacteria Solibacillus  silvestris DL3R2 and Pelomonas aquatica AIS1S isolated from Abutilon indicum and Hermocallis fulva. The seeds were sown in pots, and  growth was checked. On comparing inoculated seeds with control, it was found that the highest mean germination recorded was 2.33±0.47 at  2% salt concentration. Similarly, the maximum root length recorded is 5.3 ±0.5 at 2% lead concentration and the maximum shoot length  recorded is 23.7±2.4 at 2% salt concentration.). The maximum dry root and shoot weights recorded is 1.25±0.1 and 2.2±0.07 by the seeds  inoculated with Solibacillus silvestris DL3R2 at 2% lead concentration. The phytochemicals of the experimental plant were compared with the  in-situ plants. HPLC analysis has shown that the amount of quercetin and gallic produced at higher altitudes was 0.11%and 0.21%, which is  not very less than a plant grown at lower altitudes, i.e., 0.12% 0.22 %, respectively. The other unknown compounds detected at 254 nm were  swertiamarin, sweroside mangiferin, amarogentin, swertisin, and caffeic acid. This study provides a basis that plants can be grown under  stress conditions with the help of endophytic bacteria, thus suggesting a new step toward the conservation of plants.
Keywords: Swertia; endophytes; Solibacillus; root weight; germination